The culture of memory of Serbian builders of recent times - Kadijević Aleksandar (Nasleđe)
Within the organized culture of commemoration of artistic creators in Serbia, the least attention is arguably paid to builders of the recent era due to an insufficiently developed awareness of the artistic value of their work. Due to the technical-scientific nature of their profession and an excessive removedness from the public, they have been belatedly recognized as authoritative torchbearers of culture. The broadened scope of scientific research and a more active role of citizens in architectural heritage protection policy have, however, contributed to increased attention toward them, resulting in the erection of the first busts, memorial plaques and figural monuments to these individuals, as well as the opening of memorial rooms, the naming of streets and professional awards after them, and the expansion of lists of protected edifices designed and created by such authors. Anniversaries of meritorious builders, professional institutions and associations, as well as architects from other parts of the former Yugoslavia and abroad who left their mark on the territory of Serbia, are also commemorated. However, in spite of the progress evident, a culture of memory in terms of the architectural discipline(s) lacks organizational cohesion and consistent criteria, as well as a long-term plan for its fostering, as evident from the notable absence of such from Serbia's recently adopted National Architectural Strategy (2023-2035).